Exploring Visual Aesthetics and Immersive Cinematography in Documentary Film Production Using 360-Degree Camera Technology - Anthony Y.M. Tumimomor; Ranang Agung Sugihartono; Pande Made Sukerta; Sunardi (Academic Bright Collaboration, 2026)
Purpose – This study investigates how 360-degree camera technology transforms visual aesthetics and immersive cinematography in the documentary The Story Behind the Truck’s Screech, documenting cultural expressions displayed on truck rear panels. Methods – The study employed an exploratory qualitative design combined with experimental creative practice. Data were collected through field observation, interviews with four truck drivers, one truck painter, and one truck owner, cinematographic testing using an Insta360 X3 camera, two focus group discussions, thematic analysis, and structured expert evaluation using a five-point Likert scale. Findings – The 360-degree camera expanded conventional single-frame cinematography into omnidirectional visual capture, strengthened viewer presence, and enabled reframing techniques such as point-of-view and tiny-planet effects. Eighteen FGD participants reported greater visual freedom and immersion. Expert evaluation produced scores of 5 for attention guidance, spatial quality and composition, visual comfort, and framing uniqueness, and 4 for visual aesthetic fidelity, yielding an overall mean of 4.8 out of 5. Research implications – The findings support the practical use of 360-degree cameras in documentary production, particularly for spatially contextual cultural documentation. However, interpretation is limited by purposive sampling, a single documentary case, and context-specific production conditions. Originality – This study integrates visual ethnography, experimental cinematography, audience response, and expert assessment to demonstrate how 360-degree technology functions as both a recording tool and an aesthetic strategy in Indonesian documentary filmmaking.